2000
DOI: 10.1038/sj.ijo.0801353
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of low body mass index and high body fat percentage among Chinese, Malays and Indians in Singapore

Abstract: OBJECTIVE: To study the relationship between body fat percentage and body mass index (BMI) in three different ethnic groups in Singapore (Chinese, Malays and Indians) in order to evaluate the validity of the BMI cut-off points for obesity. DESIGN: Cross-sectional study. SUBJECTS: Two-hundred and ninety-one subjects, purposively selected to ensure adequate representation of range of age and BMI of the general adult population, with almost equal numbers from each ethnic and gender group. MEASUREMENTS: Body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
370
6
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(405 citation statements)
references
References 25 publications
25
370
6
4
Order By: Relevance
“…First, BMI does not reflect fatness uniformly in all populations and different ethnic groups 93941. The previous Omani study indicated that WHR and WC better predict CVD risk than BMI 3233.…”
Section: Discussionmentioning
confidence: 98%
“…First, BMI does not reflect fatness uniformly in all populations and different ethnic groups 93941. The previous Omani study indicated that WHR and WC better predict CVD risk than BMI 3233.…”
Section: Discussionmentioning
confidence: 98%
“…The data collected on smoking, physical activity, and diet from the self‐administered questionnaires may be subject to recall bias. Future modifications of the LS7 metrics could make BMI specific for each racial/ethnic group because some studies have demonstrated that Asians are at a higher risk of weight‐related diseases, such as CVDs, at lower BMIs 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…For any given BMI, some populations are fatter and have a more central fat distribution. 20 This has led to the recent adoption of population-specific BMI cutoff points to define obesity in some adult populations. The research on this question in children and adolescents is less advanced, but it seems likely that such population differences are not confined to adulthood.…”
Section: Evidence Base On the Comorbidities Of High Bmi For Agementioning
confidence: 99%
“…The research on this question in children and adolescents is less advanced, but it seems likely that such population differences are not confined to adulthood. 11,14,20 Ultimately, population-specific BMI cutoffs may therefore become necessary for children and adolescents. 11,14,20 Barriers to use of the BMI for age…”
Section: Evidence Base On the Comorbidities Of High Bmi For Agementioning
confidence: 99%